Chloride sensing by WNK1 regulates NLRP3 inflammasome activation and pyroptosis - Lindsey Mayes-Hopfinger (Nature Portfolio, 2021)
The serine/threonine kinase WNK1 is an inhibitor of chloride efflux. Here the authors show that this inhibition is a means of negatively regulating the activation of the NLRP3 inflammasome in macrophages, leading to reduced inflammatory responses.